Immunoglobulin A levels and its correlation with neutrophil-to-lymphocyte ratio as inflammatory biomarkers for dry eye disease in type 2 diabetes: a retrospective study - Alhalwani, Amani Y.; Abudawood, Khulud; Qadizadah, Al Baraa Ehab A.; Jambi, Shatha; Sannan, Naif S. (Frontiers in Immunology, 2023)
Background: The neutrophil-to-lymphocyte ratio (NLR) and immunoglobulin A (IgA) level are commonly used as biomarkers for inflammation. Patients with type 2 diabetes (T2D) may experience an imbalance of tear film and inflammation, which can result in dry eye disease (DED). This study aimed to assess the levels of IgA and explore its correlation with the NLR as potential inflammatory biomarkers for dry eye disease in patients with T2D. Methods: A retrospective study was conducted at the cornea clinic and diabetes centre of King Abdulaziz Medical City (Jeddah, Saudi Arabia). The study included patients with DED and the number of available T2D-DED patients determined the sample size. Neutrophil, lymphocyte, IgA and CRP (C-reactive protein) laboratory values were obtained from medical records and correlational analyses were performed. Results: The study included 85 patients with an average age of 54±14.4 years for the DED group (n=32) and 62±13.9 years for the T2D-DED group (n=53). The age difference between the two groups was statistically significant (p 0.0001). The NLR values of the T2D-DED and DED groups were 3.203±0.66 and 2.406±0.46, respectively, with no significant difference (p<0.285). Similarly, there were no significant differences in neutrophil and lymphocyte values between the two groups. The IgA levels showed no significant variation between T2D-DED and DED groups (p<0.364). Spearman's correlation analysis in the DED group showed a significant negative correlation between IgA and lymphocyte (p=0.011; r= - 0.471) values and significant positive correlations between IgA and neutrophil (p=0.014; r=0.309) and NLR (p=0.052; r= - 0.283) values. In the T2D-DED group, a significant correlation was found between IgA and CRP values (p=0.032; r=0.33). Conclusion: Although diabetic patients may exhibit higher levels of NLR and IgA that correlate with disease severity, our study did not find significant differences in NLR and IgA values between the two groups. These findings may guide future research and enhance understanding of the disease’s underlying mechanisms.